LADM-based profile for farmland Tripartite Entitlement System in China. (March 2020) - Zhuo, Yuefei; Xu, Zhongguo; Li, Guan; Liao, Rong; Lemmen, Christiaan; Wu, Cifang; Wu, Yuzhe
Highlights: The evolution process of farmland right system since the foundation of new China is summarized. The existing farmland right system after the tripartite entitlement reform is proposed. An LADM-based farmland administration system is developed. Some instance level diagrams for farmland administration activities is developed. Abstract: Since the beginning of the 21st century, China has undergone a promotion of industrialisation, urbanisation and agricultural modernisation. This promotion has triggered the mass migration of rural labour forces into cities, leading to the virtual situation of the separation of farmland contract and operation rights. To respond to this issue, the central government proposed a strategy of farmland reform in China. Such reform aims to transform the former 'Bipartite Entitlement System' into a 'Tripartite Entitlement System (TES)'. 1 Land registration provides the means for recognising formalised property rights and regulating the characteristics and transfer of land-related rights. As for farmland registration in China, it serves as a basis to explore effective forms of collective farmland ownership by implementing collective farmland ownership, stabilising farmers' contract rights and liberalising farmland operation rights. Thus, in this study, on the basis of the farmland tripartite entitlement (hereinafter referred to as 'FTE') reform in China, we develop a Land Administration Domain Model (LADM)-based TES model that will serve as the basis of subsequent system development. Specifically, first, we summarise the evolution process of China's farmland rights system since the foundation of new China. Second, we propose a farmland rights system after the FTE reform. Then, the corresponding TES model is developed based on the LADM standard and some instance-level diagrams for farmland administration activities. The new functionality of the model includes improved structuring of farmland rights and restrictions (and related source documents) and improved expansion of the land information infrastructure to rural areas.